QUALITY OF LIFE IN PATIENTS WITH CHRONIC RECURRENT LIP FISSURE - Bekdjanova O.E; Yulbarsova N.A (Scholar Express Journals, 2021)
The results of the examination of 75 patients with chronic recurrent lip fissure (CRLF) showed that long-term defects of the red border of the lips (RBL) reduce the quality of life (QOL) indicators of patients on all scales of the SF-36 questionnaire. The severity of the clinical course of the disease is synchronized with the decrease in QOL. Comparison of the average indicators of the physical (RN) and psychological (MN) components of health demonstrates a more pronounced decrease in QoL in terms of mental health. With an increase in the severity of RBL lesions, there is an aggravation and mutual aggravation of the chronic stress factor and decreased QOL, disorders of physical and mental functioning.
Keywords: Chronic recurrent lip fissure; red border of lips; depression; anxiety-phobic states